PERAN ECO-LABEL DAN GREEN BRAND IMAGE TERHADAP MINAT BELI PRODUK UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the role of eco-label and green brand image in shaping consumers’ purchase intention toward the products of Micro, Small, and Medium Enterprises (MSMEs) in Kendari City. This research employs a quantitative approach with an explanatory research design. The population consists of consumers of eco-friendly MSME products in Kendari City, with a sample of 95 respondents determined based on the number of research indicators. A purposive sampling technique was applied. Data were collected through questionnaires using a five-point Likert scale, while data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. The results indicate that eco-label and green brand image simultaneously have a positive and significant effect on purchase intention. Partially, eco-label has a positive and significant effect on purchase intention, while green brand image also has a positive and significant effect and is the most dominant variable. These findings suggest that credible environmental labelling and a strong green brand image play an important role in encouraging consumers’ intention to buy MSME products.